Oversupply of the high-cost housing in Malaysia : factors influence the developer's decision in supplying more high-cost housing / Fazilah Ramli, Rozlin Zainal and Maimunah Ali - Ramli, Fazilah; Zainal, Rozlin; Ali, Maimunah (Universiti Teknologi MARA, Perak, 2020)
High overhang of housing rates together with the price of houses offered continues to rise lead to Malaysian housing market become very unaffordable. Therefore, it is important to investigate the reason behind the developer's action in continuing to develop the high-cost housing despite the huge number of unsold housing units in the market in Malaysia. Respondents involved in this study were housing developers from Johor, Selangor and Perak who are currently or previously involved in the high-cost housing development projects that priced above RM300,000. The paper is expected that the developers able to meet the actual housing supply for high-cost housing type.